2023
DOI: 10.1007/s13167-023-00320-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential necroinflammation-associated necroptosis-related biomarkers for delayed graft function and renal allograft failure: a machine learning-based exploration in the framework of predictive, preventive, and personalized medicine

Abstract: Delayed graft function (DGF) is one of the key post-operative challenges for a subset of kidney transplantation (KTx) patients. Graft survival is significantly lower in recipients who have experienced DGF than in those who have not. Assessing the risk of chronic graft injury, predicting graft rejection, providing personalized treatment, and improving graft survival are major strategies for predictive, preventive, and personalized medicine (PPPM/3PM) to promote the development of transplant medicine. However, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…ROC curve analysis showed that our model was significant and sensitive, and was valuable in guiding the treatment and prognosis of renal transplant recipients. Among them, the AUC of risk score for 3 years of survival in the validation set is 0.852, which is better than NiNRG predictive model (AUC 0.735), which is a long-term graft survival prediction model constructed on five necroinflammation-associated necroptosis-related genes (NiNRG) [ 38 ]. In addition, our model also had better indications in long-term survival prediction at 10 years and 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…ROC curve analysis showed that our model was significant and sensitive, and was valuable in guiding the treatment and prognosis of renal transplant recipients. Among them, the AUC of risk score for 3 years of survival in the validation set is 0.852, which is better than NiNRG predictive model (AUC 0.735), which is a long-term graft survival prediction model constructed on five necroinflammation-associated necroptosis-related genes (NiNRG) [ 38 ]. In addition, our model also had better indications in long-term survival prediction at 10 years and 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Given the development of massive sequencing and genetic diagnosis techniques, it is essential to investigate the role of necroptosis in gene-based diagnostic and therapeutic strategies for DGF. It has been reported that necroptosis-related genes (NRGs) are upregulated early in the renal allograft and serve as risk factors for subsequent DGF ( 14 ). However, the association between NRGs and specific cell types or their role in the induction of specific immune responses during the process of renal IRI remains ambiguous.…”
Section: Introductionmentioning
confidence: 99%